Computational studies of shear-dependent non-newtonian droplet formation at microfluidics T-junction with experimental justification - Wong, Voon Loong (2015)
When Reynolds number (Re) is typically small, the dominant forces governing droplet formation in a microfluidic system includes surface tension, viscous, adhesion, and inertial forces, and the rheology of fluid becomes significantly important when non-Newtonian fluids are involved. The aim of this thesis is to systematically investigate the non-Newtonian shear-thinning effect of sodium carboxymethylcellulose (CMC) on the physical process of droplet formation. A two-phase conservative level-set formulation is adopted to capture the droplets breakup dynamics and relevant hydrodynamics. Detailed two-dimensional (2D) computational microfluidics flow simulations were carried out to examine systematically the influence of different controlling parameters such as degree of shear-thinning (ηo/η∞), relaxation time (λCY), flow rates (Qc, Qd), viscosities (ηc, ηd), surface wettability (θ), and interfacial tensions (σ) on CMC microdroplets formation in a Newtonian continuum. Experimental tests and numerical model justification were performed in conjunction with grid refinement to support the computational analysis and ensure its accuracy and numerical stability. The breakup process of CMC microdroplets in the cross-flowing immiscible liquids in microfluidic device with T-shaped geometry was predicted well. Data for the rheological and physical properties obeying the Carreau-Yasuda stress model were experimentally obtained to support the computational work. In present study, it is worth noting that the dynamics of shear-thinning breakup process is very sensitive to the rheological quantities (ηo/η∞, λCY) under a range of typical shear rate that associated with microchannel. The systematic variation in these rheological quantities has demonstrated different velocity profile and droplet properties. This variation significantly affects the size of droplet and breakup regime, which has never been studied previously. In contrast to previous findings based on Newtonian solutions, the dependence of flow regimes, breakup time and generation frequency on CMC polymer concentration is distinctly different in dilute and semi-dilute concentration regimes, which only exists in polymer solutions. In dilute regimes, the breakup dynamics is similar to pure Newtonian solutions, which is droplet breakup sharply at the corner of T-Junction, as the polymers are at sufficiently low concentration. Conversely, in semi-dilute regime, the presence of highly polymer molecules leads to an elongated fluid thread, a delay in breakup time, and lower production rate of droplet. Interestingly, the existence of thin polymeric filament can be observed prior to breakup for shear-thinning solution. This feature is rarely observed in Newtonian solution, but a similar phenomenon that was previously attributed to elastic effects in the fluid. Besides, the instabilities in the filament leading to the formation and breakup of satellite droplets. In the view of essential role of interfacial tension, adhesion, viscous and inertial forces, the size of shear-thinning CMC droplets is always found to be smaller than the size of Newtonian droplets as it is believed that the shear-thinning thread encounter less resistance, resulting in rapid breakup phenomenon. Present investigations enhance the understanding of the polymer structural features that govern the droplet behaviour in different flow condition. This may contributes a conceptual framework to rheological application in pharmaceutical field, especially drug delivery system, which focuses on the stability and diffusion of drug particles in dispersion into the outer fluid.